Chemical constituents from the stems of Ficus deltoideae / Ameynorsella Abdul Rashid - Abdul Rashid, Ameynorsella (Faculty of Applied Sciences, 2008)
A study of the chemical constituents of the Stems of Ficus deltoideae was conducted. The dried stems were extracted with methanol. The isolation of the compound was achieved by chromatographic techniques. Structure elucidation was performed by NMR spectroscopy, GCMS, and IR. The compound was proposed to 8-(3,4-dihydroxyphenyl)- 2-methyl-oc-7-ene-3,5 diynoic acid methyl ester.